Rule of law in India : a quest for reason - Narasappa, Harish Byrasandra, 1973- (New Delhi : Oxford University Press, 2019)
This text seeks to understand the dichotomy between the theory and practice of rule of law in India. The author argues that India's rule of law is unique in the post-colonial world encompassing many a substantive concept within it, contrary to the assertions of the liberals and thin theories. The practical challenges to the concepts of equality and certainty, both fundamental to rule of law, are explained in detail.
Previously issued in print: 2018.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on January 9, 2019).
Keywords: Rule of law -- India; Law; Laws of specific jurisdictions & specific areas of law